2012
DOI: 10.1088/0960-1317/22/3/035016
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity enhancement in inkjet-printed narrow lines through gradual heating

Abstract: Conductive silver lines of various widths (0.04-40 mm) were fabricated with dilute silver-nanoparticle ink on polyimide films using an inkjet printer. The electrical properties of the lines were found to vary in width. In particular, wider lines (>0.4 mm) exhibited low resistivity (3.6-5.4 μ cm), approaching that of bulk silver (1.6 μ cm). On the other hand, narrower lines (<0.3 mm) exhibited much higher resistivity (14.6-16.5 μ cm), presumably because of the so-called coffee-ring effect. This effect, known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…The influence of NP concentration on the obtained electrical resistivity can be due to the poor electrical contact among NPs at decreased concentrations, as well as to an overestimation of the filled volume fraction in the presence of voids, which translates into a higher apparent resistivity. A similar behavior has been reported for printed Ag lines showing a ‘coffee-ring effect’ 46 .…”
Section: Resultssupporting
confidence: 83%
“…The influence of NP concentration on the obtained electrical resistivity can be due to the poor electrical contact among NPs at decreased concentrations, as well as to an overestimation of the filled volume fraction in the presence of voids, which translates into a higher apparent resistivity. A similar behavior has been reported for printed Ag lines showing a ‘coffee-ring effect’ 46 .…”
Section: Resultssupporting
confidence: 83%
“…The point is not the circular ring but the non-uniform distribution of particles, where the inner part of the droplet endsup at a lower density. The non-uniform thickness of the colloidal film degrades the coating of paints and clarity of printed characters on paper, and the shapes of cross sections of particulate films substantially affect the electric conductivity in printed electronics [ 19 , 20 ]. The conducting wires are desired to have as low electric resistance as possible, and the elements of a heater should have a specified value of resistance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gradual heating/cooling the samples prevents crack formation by reducing the film's thermal shock. It has also been observed that the gradual heating/cooling improves film thickness uniformity [5]. It is likely that the total drying time could be reduced through process optimization, but this was not the focus of the current work.…”
Section: Drying Silver Filmsmentioning
confidence: 97%